Home advantage in professional tennis - Koning, R. H. (Journal of Sports Sciences, 2011)
Home advantage is a pervasive phenomenon in sport. It has been established in team sports such as basketball, baseball, American football, and European soccer. Attention to home advantage in individual sports has so far been limited. The aim of this study was to examine home advantage in professional tennis. Match-level data are used to measure home advantage. The test used is based on logit models, and consistent specification is addressed explicitly. Depending on the interpretation of home advantage, restrictions on the specification of the model need to be imposed. We find that although significant home advantage exists for men, the performance of women tennis players appears to be unaffected by home advantage.